PENGARUH PELAKSANAAN KOMPENSASI NON FINANSIAL TERHADAP SEMANGAT KERJA ANGGOTA GUNA MENDUKUNG KETAHANAN SATUAN (Studi di Pussenkav Kodiklat TNI AD) - , Mitro Prihantoro; , Prof. Drs. Kasto, MA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research was conducted on the base of indication member or employee working spirit level at the cavalry weaponry center office declined. Problem is suspected by the application of non financial compensation that has not happen optimally. The method of this research is a explanatory survey with quantitative and qualitative approach, which are meant to know the implementation of non financial compensation and variable of non financial compensation as well as large of influences members working spirit into the unit resilience support. The results obtained based on respondents response reaches 78.31%, meaning that non financial compensation has been done well against members in Pussenkav Kodiklat TNI AD. Although such policies are still found cause unrest against members that are not conducive working atmosphere, especially in terms of rule of law against the norm still exists in the workspace and facilities there are several things that must be considered primarily in terms of comparison of the number of people in the room with a spacious room used so seem narrower and less comfortable. The working spirit members at the cavalry weaponry center included in the category of fairly, This is proved by the acquisition of the respondents answer that is equal to 75.90%, meaning that the members at the cavalry weaponry center already have pretty good working spirit. Next the calculation results obtained coefficient of determination of the influence of non financial compensation variables on morale of the members is 44.3% while the other is not examined the effect has a magnitude of effect of 55.7%. Conclusion of this results that non financial compensation is a variable effective enough to influence and to improve employee working spirit, especially members of the cavalry weaponry center. Implications of the results of this research note that the better non financial compensation implemented it will further improve working spirit. Expectations from this research that the variable non financial compensation can be applied to the object of research in an effort to improve working spirit in the cavalry weaponry center office and the unit resilience support.